TEACHING STUDENT’S READING COMPREHENSION THROUGH PICTURE OF NARRATIVE TEXT - Ahmad Mustamir Waris; Srifani Simbuka; Nikmala Nemin Kaharuddin; Eka Putra Monoarfa (Universitas Muhammadiyah Gorontalo, 2020)
This research aims to find out the benefits of teaching reading comprehension through picture of narrative text and to find out the problems of teaching reading comprehension through picture of narrative text. The researcher used qualitative method by using observation, interview and documentation to collect the dat. During the study, the researcher employed three steps of actions. The first action is to observe the students and teachers and the last action is to collect documents from the teacher. The result shows that the benefits of pictures motivate the students to read, help students in learning, useful in teaching and learning process makes students easily to do exercise and improve students’ standard completeness score which stated as KKM 76. While the problems is the story of the text which is too unfamiliar; the students get difficulty in thinking, they do not understand the meaning of the text, unfamiliar words, and they have a poor reading technique. The main cause of the problems is the lack of vocabulary. Keywords: reading comprehension, narrattiv text, and picture